Cyrillic Versions of Piotr Skarga’s “Żywoty Świętych”: Archaeographic Survey of the Manuscript Sources and Textual Publications - Сапожникова, Галина Николаевна Николаевна (Slavistica Vilnensis, 2018)
[full article, abstract in Russian; abstract in Lithuanian and English]The article aims to summarize the scholarly information on the manuscripts that contain Cyrillic (written in Ruthenian and Old Church Slavonic) versions of the Polish edition “Lives of Saints” written by Piotr Skarga, the first Rector of Vilnius University (Piotr Skarga, Żywoty Świętych, Wilno, 1579). These versions belong to the Cyrillic tradition of the Grand Duchy of Lithuania and the Kingdom of Poland. The article presents the possibly complete list of manuscripts which contain Cyrillis versions of Skarga’s texts and their scholarly editions. The list has been compiled with regard to the latest researches.
Keywords: East Slavic hagiography, Piotr Skarga, “Żywoty Świętych”, Ruthenian translations from Polish, Old Church Slavonic translations from Polish